“The Harmony of Faith and Knowledge”: Science as an Instrument of Religious Emancipation in Hungary in the 19th-20th Centuries - LÁNYI, Gábor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The experience of Hungarian Protestants during the Counter-Reformation was that their influential aristocratic supporters played a key role in their survival. Therefore, especially after the Austro-Hungarian Compromise of 1867, which ensured their equality of rights with Catholics, their churches instinctively sought to place their lay leaders to higher political and public offices, or vice versa, to recruit their lay and even church leaders from the ruling political elite, which created a close interdependence between the Reformed Church and the political establishment of the national liberal dualist era. Gaining positions in the political arena was also linked to gains in other areas of social life such as education, culture, and science. And vice versa: gaining influence in the fields of education, culture, and science also carried political weight and recognition and unconsciously reinforced the sense of social and legal security of the Hungarian Reformed. In our study, we present three mosaic pieces of the Hungarian Reformed connections to the academic world. The first one is an analysis of the growth of Reformed university professors between 1848 and 1945. The second is a presentation of the thought of a Reformed scholar, church leader, and public figure, István Bernát, on the relationship between religion and science. Lastly, the third one is a discourse of confessionalist church reformers following the First World War, on the founding of their own Reformed academy of sciences.